Inhibition of Astrocytic Glutamine Synthetase by Lead is Associated with a Slowed Clearance of Hydrogen Peroxide by the Glutathione System - Robinson, Stephen R.; Lee, Alan; Bishop, Glenda M.; Czerwinska, Hania; Dringen, Ralf (Frontiers in Integrative Neuroscience, 2015)
Lead intoxication in humans is characterised by cognitive impairments, particularly in the domain of memory, where evidence indicates that glutamatergic neurotransmission may be impacted. Animal and cell culture studies have shown that lead decreases the expression and activity of glutamine synthetase (GS) in astrocytes, yet the basis of this effect is uncertain. To investigate the mechanism responsible, the present study exposed primary astrocyte cultures to a range of concentrations of lead acetate (0-330 μM) for up to 24 h. GS activity was significantly reduced in cells following 24 h incubation with 100 or 330 μM lead acetate. However, no reduction in GS activity was detected when astrocytic lysates were co-incubated with lead acetate, suggesting that the mechanism is not due to a direct interaction and involves intact cells. Since GS is highly sensitive to oxidative stress, the capacity of lead to inhibit the clearance of hydrogen peroxide (H2O2) was investigated. It was found that exposure to lead significantly diminished the capacity of astrocytes to degrade H2O2, and that this was due to a reduction in the effectiveness of the glutathione system, rather than to catalase. These results suggest that the inhibition of GS activity in lead poisoning is a consequence of slowed H2O2 clearance, and supports the glutathione pathway as a primary therapeutic target.